Stacking Sequence Effects on Performance of Composite Laminate Structure Subjected to Multi-Axial Quasi-Static Loading - Mohamad D.; Syamsir A.; Sa'Don S.N.; Zahari N.M.; Seman S.A.H.A.; Razali M.F.; Abas A.; Ng F.C. (Institute of Physics Publishing, 2023)
Composite structures; Laminated composites; Manufacture; Paper laminates; Structure (composition); Composite laminate; Damage development; Damage formation; Failure criteria; Mechanical performance; Quasi-static loading; Stacking sequence; Static displacement; Loading